PENGARUH PENGUNGKAPAN CORPORATE SOCIAL REPONSIBILITY TERHADAP NILAI PERUSAHAAN SUB SEKTOR GROSIR - Lay, Gabriela Natalia (Business Accounting Review, 2015)
This research was done in order to know the influence of Corporate Social Responsibility (CSR) on the firm value in wholesale sector. CSR was measured by using Global Reporting Initiative (GRI) Index 3.1 and firm value was measured by using TobinsQ. There were 3 control variables in this research, which were firm size, market share, and debt to equity ratio. Sample used in this research was taken from 78 companies years in the wholesale sector during 2009-2013.The result showed that CSR and debt to equity ratio had no significant influence on the firm value. While firm size had negative influence on the firm value and market share had significant influence on the firm value.